Preoperative prediction of macrophage infiltration by 3‐D tomographic ultrasound in endoarterectomized carotid plaques in elderly patients. Issue 4 (21st December 2012) - Koyama, Shun‐ichi; Hashimoto, Takao; Umahara, Takahiko; Akai, Tomotaka; Watanabe, Daisuke; Akimoto, Jiro; Nagao, Toshitaka; Uchihara, Toshiki; Haraoka, Jo; Iwamoto, Toshihiko
<x xml:space="preserve">Abstract</x> Aim Assessment of plaque characteristics is important for the optimal treatment of carotid stenosis, particularly in elderly patients. Macrophage infiltration is reported to be involved in carotid plaque instability. However, immunohistochemical assessment of the detailed localization of macrophage infiltration in carotid plaques remains limited. We attempted to elucidate this using 3‐D ultrasonography (3D‐US). We compared findings of the detailed localization of macrophage infiltration with findings from the newly developed tomographic ultrasound imaging (TUI). Methods We obtained specimens of carotid arteries from 18 patients undergoing carotid endarterectomy (CEA), and investigated the localization of macrophages and vascular smooth muscle cells. Their localization obtained from 11 patients was compared with their preoperative TUI findings. Results We classified the localization of macrophage infiltration into four types: (i) focal infiltration in the thick fibrous cap (12 cases); (ii) subendothelial zonal infiltration (2 cases); (iii) peripheral infiltration around the lipid core (8 cases); and (iv) local infiltration near the shoulder of the fibrous cap (2 cases). Among them, preoperative TUI was available in 11 CEA cases for histological comparison. We identified two sites of focal macrophage infiltration that corresponded to local echogenic lesions without an acoustic shadow on TUI. The proliferation of smooth muscle cells failed to show an apparent echogenicity. Conclusions TUI could not only evaluate the morphological features, but also showed the two types of focal macrophage infiltration relevant to plaque instability as an echogenic focus. TUI carried out by 3D‐US is an easily applicable and non‐invasive method that is considered useful for evaluating carotid plaques in elderly patients. Geriatr Gerontol Int 2013; 13: 834–841.